Oscillatory Criteria for Some non Conformable Differential Equation with Damping - Valdes, Juan E. N 'apoles (Discontinuity, Nonlinearity, and Complexity, 2026)
In this paper we present some criteria on the oscillation of solutions of a Non Conformable Differential Equations of α+α order, under natural considerations. The local derivative considered was defined by the author in a previous work and a change of variables is used to transform the generalized differential equation into an ordinary differential equation of second order and using a Generalized Riccatti Transformation, together with known integration techniques, we obtain the desired results.